Republic of Poland : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency Module for the Republic of Poland. The original ROSC concluded that boundaries of the general government were well defined by the public finance law, but proliferation of extrabudgetary funds and agencies had complicated transparency. Since then, four state agencies were liquidated in 2002, and their activities were taken over by other agencies or line ministries. Also, the National Labor Office was consolidated with the Ministry of Labor.